Rhesus macaques with an OPA1 mutation demonstrate features of autosomal dominant optic atrophy - Tracy N. Jaggers; Ana Ripolles-Garcia; Ala Moshiri; Brett D. Story; Jun Wang; Rui Chen; Lucy G. Moore; Leandro B. C. Teixeira; Jaeho Shim; Ana C. Raposo; Maria Isabel Casanova; Sophie M. Le; et al. (Proceedings of the National Academy of Sciences, 2026)
Autosomal dominant optic atrophy (ADOA) is an inherited optic neuropathy primarily caused by mutations in OPA1 . We identified and defined a spontaneous nonhuman primate (NHP) model of ADOA using rhesus macaques heterozygous for a missense mutation ( OPA1 A8S). With ocular examinations, ophthalmic imaging, electroretinography, histopathology, immunohistochemistry, and transmission electron microscopy (TEM), we documented retinal nerve fiber layer (RNFL) thinning, retinal ganglion cell (RGC) loss and dysfunction, OPA1 mislocalization, and reduced axonal mitochondrial density in affected macaques. Our investigation revealed substantial phenotypic variability among affected macaques, shedding light on the pathogenesis of ADOA. The retinas were evaluated using techniques such as spectral-domain optical coherence tomography and fundus photography facilitating observation of structural changes in the retina and optic nerve. Thinning of the RNFL and optic nerve head degeneration, hallmark features of ADOA, were observed in affected macaques. Decreased RGC function in the OPA1 heterozygotes was demonstrated with pattern electroretinography. Histopathological analysis and immunohistochemical staining of postmortem retinal tissue suggested RGC loss in the papillomacular bundle, with reduced OPA1 and mitochondria in the RGC axons, indicating dysfunctional mitochondrial dynamics and reduced function consistent with ADOA. Ultrastructural changes were evident with TEM including dysmorphic mitochondria, axonal loss, myelin disruption, and hypertrophic astrocytic processes. The observed similar pattern of RGC loss and dysfunction coupled with phenotypic heterogeneity in our NHP model reflects the clinical variability observed in human ADOA patients indicating that therapeutic interventions in this foveate model will likely translate to the human condition.